To Find the Comparison of Non-Split Domination Number, The Average Distance and The Diameter of Circular-Arc Graphs (International Journal of Engineering and Computer Science, 2017)
A connected dominating set is used as a backbone for communications and vertices that are not in this set communicate by passingmessage through neighbors that are in the set. Among the various applications of the theory of domination and the distance, the most oftendiscussed is a communication network. This network consists of communication links all distance between affixed set of sites. Circular-arcgraphs are rich in combinatorial structures and have found applications in several disciplines such as Biology, Ecology, Psychology, Trafficcontrol, Genetics, Computer sciences and particularly useful in cyclic scheduling and computer storage allocation problems etc. Supposecommunication network does not work due to link failure. Then the problem is what is the fewest number of communication links such that atleast one additional transmitter would be required in order that communication with all sites as possible. This leads to the introducing of theconcept of the non-split domination number, average distance and diameter. In this paper we present the comparison of non-split dominationnumber, the average distance and the diameter of circular-arc graphs.